DANCE FOLK SONGS IN KURDISH CULTURE - Rashid, Masoad Jamel (Journal of Duhok University, 2018)
Dance Folk songs are regarded one of the most important types of the song for the Kurdish people; Kurds have been interested in them and have been singing them in weddings for hunred years. Regarding to the content, these songs are simple and easy, but in terms of the template they are complex and have different forms and patterns. So far, the templates of these songs have not been studied in depth, so this research, entitled as "The Main Templates of Kurmanji Dance Folk Songs," examines the main templates and patterns of Kurmanji Dance Folk songs. The researcher has identified the main templates of 2015 songs, classified by templates. On the other hand, for each template, the number of songs that systemized on eachtemplate, has been identified altogether with its percentage. In conclusion, the researcher came to a number of results, the most important of which is that Kurmanji Dance Folk songs have many complex templates, and these templates are distributed into two types: the main templates and special templates, in addition to a few songs that do not have certain templates